Use of HPLC/UPLC-spectrophotometry for detection of formazan in in vitro Reconstructed human Tissue (RhT)-based test methods employing the MTT-reduction assay to expand their applicability to strongly coloured test chemicals. Issue 4 (June 2015) - Alépée, N.; Barroso, J.; De Smedt, A.; De Wever, B.; Hibatallah, J.; Klaric, M.; Mewes, K.R.; Millet, M.; Pfannenbecker, U.; Tailhardat, M.; Templier, M.; McNamee, P.
Highlights Key qualification parameters defined for HPLC/UPLC-spectrophotometry systems. HPLC/UPLC-spectrophotometry for formazan detection is highly reproducible. High concordance of classification using OD and HPLC/UPLC-spectrophotometry. Applicable for highly coloured chemicals interfering with standard detection method. Applicable to in vitro RhT test methods for eye/skin irritation and skin corrosion.